Challenging the Arthurian myth in fanfiction: rethinking gender and leadership - Anastasia, Sharapkova (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper explores the Arthurian myth challenged in fanfiction. The quintessentially masculine character – King Arthur, is regendered as a woman, thus addressing the representations of power and leadership closely associated with masculinity in the mythological world. However, gender transformation is not just about archaic stereotypes but about the real-world inequalities and the burden of responsibility many contemporary women are trying to balance with their personal lives. The significance of the study lies in scrutinizing the modern female leadership role constructed through reference to old stories. Seventeen stories published in 2007–2020 (fanfiction.net) were analysed through cognitive linguistic methodology. They feature three major pathways the regendering may take: the Warrior, the Queen, and the Mother-nature type being organically woven into the canonical narrative. Fanfiction authors downplay the brutality of the archaic world and bring a hardworking and intelligent ruler to the fore. Many female characters in the stories suffer from the need to conform to the rules of the old trade yet become successful warriors and rulers. We also show that deconstructing one of the core characteristics of King Arthur’s image tends to reinforce the others: social position, detailed description of place and time, and following the plot meticulously. The English linguistic repertoire used to describe the regendered character is also reinforced, with keywords commonly used to describe King Arthur being repeated at key points in the narrative.